McHarg's methodology of analysis and diagnosis applied to rural planning in the Teixeira Soares river basin, RS, Brazil (Terr@ Plural, 2021)
This paper seeks to characterize, analyze and diagnose the Teixeira Soares River basin based on the methodology of analysis and diagnosis proposed by Ian McHarg (1992). It is found that the region presents a weakening of rural communities, in addition to difficulty and instability in issues related to food production and environmental conservation. The form of production that was tried to be inserted may be interfering in the local landscape and causing a shortage of natural soil fertility and an imbalance in the fauna, flora, and water of the hydrographic basin. In the end, we understand the need to plan rural areas, as a way to relate all the aspects inserted in it, from the aspects related to the geobiophysical support to the anthropic ones. In order to enhance rural production and bring local society closer to the natural environment, guidelines are proposed for the qualification of the spaces that comprise the sub-basin.
Keywords: GIS; Rural Landscape; Environmental Sustainability